Leverage and Risk Taking under Moral Hazard - Christian Hott (Journal of Financial Services Research, 2021)
In this paper, I analyze the effectiveness of different capital regulations in mitigating the effects of moral hazard that exists only for systemically important banks. Leverage restrictions have the potential to reduce the fraction of banks that are systemically important but do not mitigate moral hazard for those that are. Risk adjusted requirements could mitigate moral hazard (of banks with low leverage) but do not affect (endogenous) systemic risk. A combination of both requirements as proposed by the Basel III framework can be successful, although only under restrictive conditions.
Keywords: G21; G28; 330; Capital regulation; Moral hazard; Leverage